Análisis correlacional entre el sistema de gestión de calidad bajo un rol gerencial y el despliegue administrativo en la Sede Vacacional Los Trupillos del Círculo de Suboficiales de las Fuerzas Militares. (2020)
The organizational management and development of the competitiveness of an organization is directly linked to the administrative process, therefore, the concept that the tasks and activities associated with the performance of the managerial role, such as planning, organization, direction and control, is considered valid. They allow the coordination of multi-system mechanisms to guide a comprehensive quality policy. From this position, a clear correlation is associated between the work implemented at the level of a quality management system and the role of the manager, therefore, it is important to integrate the competencies, information and actions so that the development of the quality management model and the organizational strategic plan are coherent. The aim of this study is to outline the correlation between the technical quality management systems and the performance of the manager role at the Los Trupillos Vacation Venue.